PENGARUH PEMBERIAN EKSTRAK KUNYIT (Curcumin domestica Val.) TERFERMENTASI TERHADAP KOMPOSISI FISIK KARKAS BURUNG PUYUH (Cortunix cortunix Japanica) - M. S. N. Beme; G. A. M. K. Dewi; M. Wirapartha (Fakultas Peternakan Universitas Udayana, 2025)
In chicken feed, notably quail feed, turmeric (Curcuma longa) is frequently used in place of antimicrobial growth promoters. Low dosages of turmeric, an antibiotic, are used to improve animal growth and output. Analyzing the effects of supplementing with fermented turmeric extract on the slaughter weight, carcass weight, and percentage of physical content of quail carcasses (Coturnix coturnix japonica) was the aim based on this study. The investigation was carried out at the Faculty of Animal Science's Sesetan Farm in Denpasar, Bali. Fermented turmeric extract was added to drinking water as the therapy in this trial, which employed a completely randomized design (CRD). The following were the treatments: P0 (control, which was water supplied without fermented turmeric extract), P1 (drinking water containing 1% fermented turmeric extract), and P2 (drinking water containing 2% enzyme). Drinking water containing 1% fermented turmeric extract, P2 (drinking water containing 2% fermented turmeric extract), P3 (drinking water containing 3% fermented turmeric extract), and P0 (control, without fermented turmeric extract) were the treatments. Slaughter weight, carcass weight, and the carcass's physical composition—which includes the proportion of meat, skin, fat, and bone—were the parameters that were measured. The percentage of meat in the quail carcass's physical composition was significantly impacted by the addition of fermented turmeric extract at levels of 1%, 2%, and 3%, according to the results (P<0.05). Slaughter weight, carcass weight, and various carcass physical composition percentages, such as skin, fat, and bone percentages, did not, however, alter significantly as a result of this therapy. According to the study's findings, the percentages of skin and fat, slaughter weight, carcass weight, and bone percentage were not significantly impacted by the 1%, 2%, and 3% of fermented turmeric extract added to drinking water. The percentage of meat in the physical makeup of quail carcasses, however, was significantly impacted by treatments at the 2% (P2) and 3% (P3) levels. ABSTRAK Kunyit (Curcuma longa) kerap menjadi alternatif yang menggantikan antibiotic growth promoter pada pakan unggas, termasuk burung puyuh. Kunyit merupakan antibiotik yang ditambahkan dalam dosis rendah untuk meningkatkan pertumbuhan dan produktivitas ternak. Tujuan dari penelitian ini adalah untuk menganalisis dampak pemberian ekstrak kunyit terfermentasi pada bobot potong, bobot karkas, dan persentase komposisi fisik karkas burung puyuh (Coturnix coturnix japonica). Studi ini dilakukan di Peternakan Sesetan, Fakultas Peternakan, Denpasar, Bali. Studi ini menggunakan Rancangan Acak Lengkap (RAL), dimana perlakuan yang diberikan adalah pencampuran ekstrak kunyit yang telah difermentasi ke air minum. Perlakuan terdiri dari: P0 (kontrol, tanpa ekstrak kunyit fermentasi), P1 (air minum dengan ekstrak kunyit fermentasi 1%), P2 (air minum dengan ekstrak kunyit fermentasi 2%), dan P3 (air minum dengan ekstrak kunyit fermentasi 3%). Parameter yang diamati yaitu bobot potong, bobot karkas, dan persentase komposisi fisik karkas yang terdiri dari persentase daging, kulit dan lemak serta tulang. Hasil menunjukkan bahwa penambahan ekstrak kunyit terfermentasi pada level 1%, 2%, dan 3% berpengaruh nyata terhadap persentase daging pada komposisi fisik karkas puyuh (P<0,05). Namun perlakuan tersebut tidak menunjukkan perbedaan yang nyata terhadap bobot potong, bobot karkas, maupun persentase komposisi fisik karkas yang lain, seperti persentase kulit dan lemak serta tulang. Berdasarkan hasil penelitian, pemberian ekstrak kunyit terfermentasi melalui air minum dengan level 1%, 2%, serta 3% tidak memberikan pengaruh signifikan pada bobot potong, bobot karkas, persentase tulang, maupun persentase kulit dan lemak. Akan tetapi, perlakuan pada level 2% (P2) dan 3% (P3) menunjukkan pengaruh nyata terhadap persentase daging dalam komposisi fisik karkas burung puyuh.